1985
DOI: 10.1002/ijc.2910350213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fibronectin synthesis and binding distribution in SV40‐transformed human keratinocytes

Abstract: We have studied the synthesis and distribution of fibronectin in human epidermal keratinocytes infected by SV40, a system in which the acquisition of transformed properties occurs in a sequential and progressive manner. Immunofluorescence studies showed that cultured uninfected keratinocytes do not exhibit fibronectin on the superficial cell surface, but that virus-infected cells come to display superficial fibronectin-containing cables in a density-dependent manner after a certain point in the transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
6
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…between lack of fibronectin and malignant behavior need not be of general validity. This is further substantiated by a recent report on the increased fibronectin synthesis and deposition in human keratinocytes during a multistep viral transformation process [28]. However, in the latter study transformation was accompanied by a loss of cell polarity, inasmuch as normal keratinocytes only showed fibronectin on the basal cell surface, whereas the transformed cells bound fibronectin to the upper surface as well.…”
supporting
confidence: 68%
“…between lack of fibronectin and malignant behavior need not be of general validity. This is further substantiated by a recent report on the increased fibronectin synthesis and deposition in human keratinocytes during a multistep viral transformation process [28]. However, in the latter study transformation was accompanied by a loss of cell polarity, inasmuch as normal keratinocytes only showed fibronectin on the basal cell surface, whereas the transformed cells bound fibronectin to the upper surface as well.…”
supporting
confidence: 68%
“…However, these findings are consistent with the idea that heparan sulphate, by virtue of its ability to interact with other ECM components, plays an important role in promoting overall matrix stability; since the transformed keratinocytes retain an ECM (Brown & Parkinson, 1984Bernard et al, 1985;Edelman et al, 1985), whereas most other transformed cells do not (Alitalo & Vaheri, 1982).…”
supporting
confidence: 83%
“…It is therefore probable that interactions between heparan sulphate and other ECM components are relatively undisrupted in transformed keratinocytes. This, and previous reports on the ECM of transformed keratinocytes in vitro (Brown & Parkinson, 1984Bernard et al, 1985;Edelman et al, 1985) imply that malignant transformation of the keratinocyte requires the continued (or even increased) production of an intact and functional ECM. This proposal is in agreement with a recent report which showed that even invading SCCs retain basement membrane production, as demonstrated by immunohistochemical staining for type IV collagen (Gusterson et al, 1984), and with other reports of an apparent increase in fibronectin (Nelson et al, 1983;Grimwood et al, 1984) and laminin (Nelson et al, 1983) production in basal cell carcinomas.…”
supporting
confidence: 65%
“…Since that date there have been several investigations on the in vitro effects of SV40 on human keratinocytes (Taylor-Papadimitriou et al, 1982;BanksSchlegel & Howley, 1983;Rhim et al, 1985). SV40 has been shown to immortalise keratinocytes, to impair their ability to follow the normal pathway to terminal differentiation, to alter their response to tumour promoters, to decrease their growth requirements in vitro and to induce several other phenotypic alterations, including changes in keratin profiles, the actin cytoskeleton and the extracellular matrix (Steinberg & Defendi, 1979, 1985Taylor-Papadimitriou et al, 1982;Banks-Schlegel & Howley, 1983;Rhim et al, 1985;Parkinson et al, 1983Parkinson et al, , 1984Hronis et al, 1984;Bernard et al, 1985; Brown & Parkinson, 1984;Edelman et al, 1985;Defendi et al, 1982).…”
mentioning
confidence: 99%